Evaluation of prophylactic dosages of Enoxaparin in non-surgical elderly patients with renal impairment - Nibal Chamoun; Hady Ghanem; Ahmad Hachem; Essa Hariri; Christelle Lteif; Hanine Mansour; Hani Dimassi; Richard Zalloum; Georges Ghanem (BMC, 2019)
Abstract Background Thromboprophylaxis dosing strategies using enoxaparin in elderly patients with renal disease are limited, while dose adjustments or monitoring of anti-Xa levels are recommended. We sought to evaluate the efficacy and safety of enoxaparin 20 mg versus 30 mg subcutaneously daily by comparing anti-Xa levels, thrombosis and bleeding. Methods We conducted a prospective, single-blinded, single-center randomized clinical trial including non-surgical patients, 70 years of age or older, with renal disease requiring thromboprophylaxis. Patients were randomized to receive either 20 mg or 30 mg of enoxaparin. The primary endpoint was peak anti-Xa levels on day 3. Secondary endpoints included trough anti-Xa levels on day 3, achievement of within range prophylactic target peak anti-Xa levels and the occurrence of hemorrhage, thrombosis, thrombocytopenia or hyperkalemia during hospitalization. Results Thirty-two patients were recruited and sixteen patients were randomized to each arm. Mean peak anti-Xa level was significantly higher in 30 mg arm (n = 13) compared to the 20 mg arm (n = 11) 0.26 ± 0.11, 95%CI (0.18-0.34), versus 0.14 ± 0.09, 95CI (0.08-0.19) UI/ml, respectively; p = 0.004. Mean trough anti-Xa level was higher in 30 mg arm (n = 10) compared to the 20 mg arm (n = 16), 0.06 ± 0.03, 95CI (0.04-0.08) versus 0.03 ± 0.03, 95CI (0.01-0.05) UI/ml, respectively; p = 0.044. Bleeding events reported in the 30 mg arm were one retroperitoneal bleed requiring multiple transfusions, and in the 20 mg arm one hematuria. No thrombotic events were reported. Conclusion Peak anti-Xa levels provided by enoxaparin 20 mg were lower than the desired range for thromboprophylaxis in comparison to enoxaparin 30 mg. Trial registration The trial was retrospectively registered on ClinicalTrials.gov identifier: NCT03158792. Registered: May 18, 2017.